2020
DOI: 10.1152/ajpregu.00341.2019
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of moderate exercise and short-term fasting on markers of immune function in healthy human subjects

Abstract: This study aimed to investigate the effects of a short-term (36 h) fasting period combined with an acute bout of exercise on markers of immune function and inflammation in healthy human subjects. Fourteen moderately trained male subjects (aged 19–39 yr) participated in a 36-h fasting trial (FA-T), followed by an acute bout of moderate exercise (60% V̇o2max). After 1 wk, the same subjects, as their own control, participated in a nonfasting trial (NFA-T) in which they performed an exercise trial of the same dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In the study by Catoire et al, CCL2 was identified as a myokine whose expression in muscle and plasma level increases after 1-h one-legged acute exercise [ 12 ]. What is more, increased plasma levels of CCL2 were found in female rowers after 1 h of endurance exercise [ 48 ] and in males subjected to 36 h fasting trial and a subsequent acute bout of moderate exercise [ 49 ]. Zwetsloot et al noted that a single acute session of high-intensity interval training (HIIT) (60 s, at 100% VO 2 max) in active young men led to an increase in several inflammatory cytokines and chemokines, such as IL-6, IL-8, IL-10, TNF-α, and MCP-1 (CCL2) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Catoire et al, CCL2 was identified as a myokine whose expression in muscle and plasma level increases after 1-h one-legged acute exercise [ 12 ]. What is more, increased plasma levels of CCL2 were found in female rowers after 1 h of endurance exercise [ 48 ] and in males subjected to 36 h fasting trial and a subsequent acute bout of moderate exercise [ 49 ]. Zwetsloot et al noted that a single acute session of high-intensity interval training (HIIT) (60 s, at 100% VO 2 max) in active young men led to an increase in several inflammatory cytokines and chemokines, such as IL-6, IL-8, IL-10, TNF-α, and MCP-1 (CCL2) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the effect of exercise in healthy individuals, remarkable efficacy has been found in people with underlying diseases (e.g., high blood pressure, heart disease, diabetes, and cancer) and the elderly, who are generally more prone to infections (30)(31)(32). Therefore, regular moderate-intensity activity helps maintain fit and healthy within the recommended guidelines (31).…”
Section: The Effect Of Exercise On the Immune Systemmentioning
confidence: 99%
“…In addition to the effect of exercise in healthy individuals, remarkable efficacy has been found in people with underlying diseases (e.g., high blood pressure, heart disease, diabetes, and cancer) and the elderly, who are generally more prone to infections (30)(31)(32). Therefore, regular moderate-intensity activity helps maintain fit and healthy within the recommended guidelines (31). Regu-lar moderate-intensity exercise promotes the immune response, dysfunctional T cells (33), T cell proliferation, circulating inflammatory cytokine levels (18,33), neutrophil phagocytic activity, cytotoxic activity, and IL-2 production (34).…”
Section: The Effect Of Exercise On the Immune Systemmentioning
confidence: 99%